STUDI TENTANG STRATEGI GURU DALAM PEMBELAJARAN MATEMATIKA MENYIKAPI PERGESERAN PARADIGMA PENDIDIKAN TEACHER CENTERED KE STUDENT CENTERED - Listyani, Endang (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2007)
Educational system in Indonesia has been changing from teacher centered to student centered paradigm. The teacher leads to have an important responsibility to involve in the paradigm changing. Regarding that responsibility, the teacher must have a competency to use the appropriate learning strategy that can engage the student activity in class. The propose of this research is to know the teacher strategy in mathematics learning toward the changing of educational paradigm from teacher centered to student centered. The respondents in this research are the entire mathematics teachers in SMA Negeri at Kotamadya Yogyakarta consisting of 11 schools. Each school has 3-6 mathematics teachers, so there are 56 respondents including in this study. The closed and opened questionnaires are given to the teachers. Based on the questionnaires, it will be concluded whether the teacher has applied strategy that fits to student-centered or to the teacher centered paradigm and to identify problems faced by the teacher in performing learning innovations. Considering the research result, it can be concluded that generally the mathematics teachers in SMA Negeri, Kotamadya Yogyakarta have attempted the teaching and learning strategy suitable to student centered paradigm. The problems correspond to their effort are the limited equipment and human resources capabilities. Besides that, the learning innovations need longer time, which yields the difficulties to finish all the material of the subject.Key word: The teaching and learning strategy, Student centered